Manger les produits locaux pour manger mieux - Borelli, Teresa; Grazioli, Francesca; Falcis, Eleonora de; Naino Jika, Abdel Kader; Otieno, Gloria Atieno (2022)
Within the EU-funded SUSTLIVES project, this easy to read brochure provides information on the project, project sites, the target neglected and underutilized species being studied in Niger and Burkina Faso as well as information on their importance for nutrition, climate resilience and livelihoods.